2020
DOI: 10.1101/2020.05.07.082768
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mutation landscape of SARS-CoV-2 reveals five mutually exclusive clusters of leading and trailing single nucleotide substitutions

Abstract: The COVID-19 pandemic is expanding at an unprecedented rate. As a result, diagnostic services are stretched to their limit, and there is a clear need for the provision of additional diagnostic capacity.Academic laboratories, many of which are closed due to governmental lockdowns, may be in a position to support local screening capacity by adapting their current laboratory practices. Here, we describe the process of developing a SARS-Cov2 diagnostic workflow in a conventional academic Containment Level 2 (CL2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 52 publications
3
21
0
1
Order By: Relevance
“…A very recent paper by Mishra et al identified two variant positions overlapping with this analysis in the 5’- and 3’-UTRs respectively (i.e. g.241C>T, g.29742G>A/T) ( 22 ). In this study, all UTR variants were located on predicted stem-loop structures with the exception of g.36C>T in the 5’-UTR.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…A very recent paper by Mishra et al identified two variant positions overlapping with this analysis in the 5’- and 3’-UTRs respectively (i.e. g.241C>T, g.29742G>A/T) ( 22 ). In this study, all UTR variants were located on predicted stem-loop structures with the exception of g.36C>T in the 5’-UTR.…”
Section: Resultssupporting
confidence: 55%
“…5). The first of these three, CEVg2, was detected entirely within the N protein in 22.1% of the genomes. CEVg2 consisted of three consecutive variants g.28881G>A, g.28882G>A, g.28883G>C, which together led to two amino acid substitutions, p.R203K and p.G204R, and the change from one to two positively-charged residues.…”
Section: Analysis Of Sars-cov-2 Variant Combinationsmentioning
confidence: 99%
“…Despite the limited number of SARS-CoV-2 genome sequences, our work, as well as previous studies (55,56) that used clustering techniques to study the evolution of the SARS-CoV-2 virus, has shown to be a good supplement tool in phylogenetic analyses.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, recent studies have detected high-frequency trinucleotide mutations (G28881A, G2882A, and G28883C) in the SARS-CoV-2 genome (Yao et al, 2020;Yin, 2020). G28881A and G28882A always co-occur within the same codon, which means a positive selection of amino acid (Mishra et al, 2020), but the consequence of the trinucleotide mutations was still elusive. We noticed that the trinucleotide mutations were in the G-rich sequence from 28,881 to 28,917 nt (5 ′ GGGGAACTTCTCCTGCTAGAATGGCTGGCAATGGCGG 3 ′ ).…”
Section: Discussionmentioning
confidence: 99%